Becoming Past : History in Contemporary Art - Blocker, Jane (Book collections on Project MUSE., 2015)
"Is there such a thing as contemporary art history? The contemporary, after all--as much as we may want to consider it otherwise--is being made history as it happens. By what means do we examine this moving target? These questions lie at the center of Jane Blocker's Becoming Past. The important point is not whether there is--or should be--contemporary art history, Blocker argues, but how. Focusing on a significant aspect of current art practice?in which artists have engaged with historical subject matter, methods, and inquiry?Blocker asks how the creation of the artist implicates and interrogates that of the art historian. She moves from art history to theater, to performance, and to literature as she investigates a series of works, including performances by the collaborative group Goat Island, the film Deadpan by Steve McQueen, the philosophies of science fiction writer Samuel Delany and documentary filmmaker Ross McElwee, the film Amos Fortune Road by Matthew Buckingham, and sculptures by Dario Robleto. Many books have sought to understand the key directions of contemporary art. In contrast, Becoming Past is concerned with the application of art history in the pursuit of such trends. Setting the idea of temporality decisively in the realm of art, Blocker's work is crucial for artists, art historians, curators, critics, and scholars of performance and cultural studies interested in the role of history in the practice of art."--